ChaTA: Towards an Intelligent Question-Answer Teaching Assistant using Open-Source LLMs - Hicke, Yann; Agarwal, Anmol; Ma, Qianou; Denny, Paul (arXiv, 2023)
Responding to the thousands of student questions on online QA platforms each semester has a considerable human cost, particularly in computing courses with rapidly growing enrollments. To address the challenges of scalable and intelligent question-answering (QA), we introduce an innovative solution that leverages open-source Large Language Models (LLMs) from the LLaMA-2 family to ensure data privacy. Our approach combines augmentation techniques such as retrieval augmented generation (RAG), supervised fine-tuning (SFT), and learning from human preferences data using Direct Preference Optimization (DPO). Through extensive experimentation on a Piazza dataset from an introductory CS course, comprising 10,000 QA pairs and 1,500 pairs of preference data, we demonstrate a significant 30% improvement in the quality of answers, with RAG being a particularly impactful addition. Our contributions include the development of a novel architecture for educational QA, extensive evaluations of LLM performance utilizing both human assessments and LLM-based metrics, and insights into the challenges and future directions of educational data processing. This work paves the way for the development of CHATA, an intelligent QA assistant customizable for courses with an online QA platform
Keywords: /unread; Computer Science - Artificial Intelligence; Computer Science - Computation and Language; Computer Science - Machine Learning